PELATIHAN PUBLIC SPEAKING KADER PKK KELURAHAN TANDANG KECAMATAN TEMBALANG SEMARANG - Tarcisia Sri Suwarti; Nuning Zaidah; Jafar Sodiq (Universitas PGRI Semarang, 2014)
Abstract Many people do not understand the importance of public speaking technique. The most frequent phenomenon of public speaking is in PKK (Family Welfare Guidance) as one of the organization within our closest community. Therefore, there should be a training of public speaking skills for PKK cadres of RW VI, Tandang Village, Tembalang Subdistrict, Semarang. It is expected to explore the potency of PKK cadres to improve their confidence and bravery to speak up in public. After training, it is also expected that the PKK cadres can continuously implement all of the training materials. Thus, these cadres can sharpen their ability to do public speaking in front of?é?á forum which can produce other achievements that can improve the quality of PKK cadres. It can result on the increasing of their role and involvement in every governmental or non governmental activity or program. Keywords: public speaking, PKK cadres, technique performance, giving information